Competitiveness Strategy Analysis With SWOT Approach Of Grocery Stores Islamic Business Perspective - Rizqiyani, Sabila; Sari, Aenun Mela (International Conference on Islamic Economic (ICIE), 2024)
The grocery store became one of the UMKMs that channeled everyday needs to the community. This research aims to identify strategies to improve the competitiveness of food enterprises with a SWOT analysis approach, with a case study of Rizqi Halwa Kelontong Shop in Negarayu Village, Tonjong District, Brebes District. This research uses qualitative descriptive methods. Data sources in this research include primary and secondary data. With the collection of primary data from interview and observation, Secondary data from library studies such as journals and relevant articles. The strategy to compete in enterprise is the most crucial thing in development process of enterprise, so it requires the right strategy by implementing the SWOT analyst approach. Besides, as Muslim, also need to pay attention to existence of Islamic business ethics. Islamic business ethics teaches businessmen tobe able to follow orders they are taught and avoid prohibitions in accordance with Islamic rules. SWOT analysis of grocery stores shows strength in product completeness, price flexibility, and good customer service. However, there are weaknesses such as space constraints and SDM, a less strategic location. Opportunities to expand the product sector and enhance cooperation with suppliers need to be exploited, while threats come from large-store competition and price fluctuations. Strategies that match the SWOT matrix should used to maximize strengths, minimize weaknesses, and improve the competitiveness and resilience of retail stores in the market. The owner of this store applies the principles of Islamic business ethics and always keeps practicing shiddiq, trust, fathonah, and tabligh attitudes.